Antioxidant potential and polyphenol content in different parts of Graptophyllum pictum extracts - Feda Anisah Makkiyah; Eldiza Puji Rahmi; Rini Anggi Arista; Nelly Marliani; Waras Nurcholis (Wolters Kluwer Medknow Publications, 2024)
The antioxidant potential of Graptophyllum pictum (wungu leaves), an indigenous shrub plant extensively used in traditional medicine in Indonesia, was investigated in this study. The research focused on a comprehensive evaluation of total phenolic content (TPC), total flavonoid content (TFC), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and ferric-reducing antioxidant power (FRAP) across various plant parts, including roots, stems, and flowers, which had been underexplored in prior studies. The ethanol extract derived from wungu flowers and leaves demonstrated notable antioxidant potential, characterized by elevated TPC (12.22 ± 0.31 mg GAE/g DW) and FRAP (37.73 ± 1.08 μmol TEAC/g DW) in the ethanol extract of wungu flowers. Similarly, the ethanol extract of wungu leaves showcased a substantial TFC (2.31 ± 0.18 mg QE/g DW) and DPPH (1.12 ± 0.05 μmol TEAC/g DW), surpassing other parts of the wungu plant in the same or different extracts. These findings suggested that ethanol extracts were a promising foundation for herbal medicines with antioxidant properties, highlighting their potential applications in plant breeding programs. Furthermore, the correlation data underscored the significance of the ethyl acetate and ethanol extracts, revealing a robust correlation between TPC, TFC, and FRAP compared to the n-hexane extract.